Kosmetik Herbal Bahan Alami yang Berfungsi Sebagai Pelembab Kulit Berdasarkan Kajian Pustaka - Eny Widhia Agustin; Mia Hafizah Tumangger; Azkia Sandra Nugroho; Friska Kirana Andieta Rinjani; Miftakhul Jannah Aulia’ Alvina Setyowati; Damarisa Febrina Yosheaningtyas; Desty Faticha Rachma; Kharisma Aprodita Az Zahra Putri Hiadayat (Jurnal Ventilator, 2024)
Herbal cosmetic products are increasingly being used by women nowadays because they are made from natural ingredients which have many benefits. For example, moisturizing the skin, the aim of this research is to discuss what natural ingredients can be used as ingredients in skin moisturizers. The method used in the research uses literature studies from national and international journals. The results obtained from research using this literature study show that the ingredients are natural. which contains ingredients such as hyaluronic acid and glycerin for skin moisture.